Fisioterapia Respiratoria en la Enfermedad Pulmonar Obstructiva Crónica del Adulto Mayor - García Obando, Ronny Daniel (2019)
To know the effectiveness of respiratory physiotherapy in older adults with COPD, the techniques ELTGOL, and respiratory muscle training (IMT) used to promote the elimination of secretions and improve the quality of patients’ lives. This research developed in the literature review modality. Although these applications and is techniques of ELTGOL and IMT in our work environment are not known, due to insufficient updated bibliographic material, however, it was possible to find 100 scientific articles, through the exclusion criteria and the assessment of the PEDro scale discarded for this research and only 35 scientific articles adapted to the study with an evaluation equal to or greater than 6. These articles are in different languages such as English, French, and Portuguese, with very little update information in Spanish. This research intends to demonstrate the effectiveness of respiratory physiotherapy in elderly patients with COPD with this database found in PubMed, Scielo, ScienceDirect, and Cochrane majorly. The collection of the articles was from 2000 until 2019 years. Finally and after the respective discussion of different authors, the objective was reached, showing the respiratory physiotherapy through it techniques such as ELTGOL and IMT favor the elimination of secretions, improves lung ventilation, and support the older adults quality life.